2012
DOI: 10.1103/physrevd.85.046011
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations around the AdS Born-Infeld black holes

Abstract: We study the quasinormal mode of the perturbation of the scalar field interacting with the electromagnetic field in the backgrounds of Schwarzschild AdS black hole, the Reissner-Nordstrom AdS black hole and the Born-Infeld AdS black hole. We disclose influence by the electric charge Q, the coupling between the scalar and electromagnetic field q and the Born-Infeld parameter b on the quasinormal frequencies of the scalar perturbation. We observe the possible growing mode in the perturbation when the scalar fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
(21 reference statements)
2
12
0
Order By: Relevance
“…Replacing the Maxwell field with the nonlinear electromagnetic field, it was disclosed from the behavior of the boundary operator in the CFT that the nonlinearity in Born-Infeld and the logarithmic form fields can make holographic superconductor difficult to form [19,66]. In the corresponding bulk spacetime, it was observed that the nonlinearity of the electromagnetic field can hinder the growing mode to appear in the scalar perturbation [67], which is consistent with the phenomenon on the boundary CFT. Other works on holographic dual models in the presence of nonlinear corrections to the Maxwell electrodynamics can also be found in [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Jhep02(2016)116supporting
confidence: 60%
“…Replacing the Maxwell field with the nonlinear electromagnetic field, it was disclosed from the behavior of the boundary operator in the CFT that the nonlinearity in Born-Infeld and the logarithmic form fields can make holographic superconductor difficult to form [19,66]. In the corresponding bulk spacetime, it was observed that the nonlinearity of the electromagnetic field can hinder the growing mode to appear in the scalar perturbation [67], which is consistent with the phenomenon on the boundary CFT. Other works on holographic dual models in the presence of nonlinear corrections to the Maxwell electrodynamics can also be found in [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83].…”
Section: Jhep02(2016)116supporting
confidence: 60%
“…The BI-AdS geometry and the extended studies have been explored in detail in [37][38][39][40][41][42] and references therein. Here, we only give a brief review on the BI-AdS geometry related with our present study.…”
Section: Einstein-born-infeld Black Holementioning
confidence: 99%
“…It may be noted that even though the charged scalar perturbations are important [39][40][41][42][43][44], mostly QNMs in Lifshitz theories have been studied for neutral scalar perturbations [45][46][47][48][49][50][51][52]. However, QNMs for a charged dilaton-Lifshitz solutions in the four dimensions have also been studied [53].…”
Section: Introductionmentioning
confidence: 99%